Gambaran Pengetahuan Tentang Diabetes Melitus Pada Remaja - meldawati; Cynthia Eka Fayuning Tjomiadi; Onieqie Ayu Dhea Manto (2025)
Diabetes mellitus is a disease characterized by high blood sugar levels due to the accumulation of unhealthy lifestyles since adolescence. Behavior including prevention and treatment of diabetes mellitus depends on adolescents' knowledge about diabetes so it needs to be studied. This study aims to describe knowledge about diabetes mellitus in adolescents in the working area of ​​Martapura 1 Health Center, Banjar Regency. This quantitative research with a descriptive analytical design was conducted on 30 adolescents in the working area of ​​Martapura 1 Health Center, Banjar Regency who were selected using purposive sampling techniques using questionnaires and analyzed using univariate techniques. The majority of respondents, 12 out of 30 (40%) were in the early adolescent age group (10-14 years) and the majority of respondents, 19 out of 30 (60%) were male. The majority of respondents, 17 out of 30 (56.7%) were identified as having insufficient knowledge about diabetes mellitus. Health education about diabetes mellitus in adolescents needs to be improved by utilizing digital media and peer approach methods.